Entscheidungsunterstützte Methodik zur Produktkonzeptauswahl : Grundlagen, Systematik und exemplarische Anwendung - Schubert, Peter (KIT Scientific Publishing, 2015)
The present monograph addresses the decision problem of product concept selection. It is constructed as a multi-criteria decision model spanning the dimensions benefits, costs, opportunities and risks, while each dimension represents a decision network. To focus economic aspects target costing and activity based costing have been incorporated into the methodology. The evaluation logic is based on the analytic network process, amended and modified by the fuzzy set theory.